Pemberdayaan Masyarakat Dalam Mewujudkan Kabupaten Banyuwangi Sehat - Nur Anim Jauhariyah; Nurul Inayah (IAI Darussalam, 2020)
Healthy Regency / City is an effort to create a district / city condition that is clean, comfortable, safe and healthy for residents to live in, which is achieved through implementing several integrated arrangements and activities agreed upon by the community and local government. Banyuwangi Regency has participated in this activity which started in 2011 ago. The District Forum in Banyuwangi Regency, which has been formed with the support of the Pokja Desa / healthy kelurahan, has carried out activities according to the 6 indicators that are currently being followed by Banyuwangi Regency. Coaching activities are carried out in incidental meetings during forum visits to the District. Activities during the Covid 19 pandemic in 2020 were more dominated by social activities such as distributing masks, hand sanitizers, spraying disinfectants in public places as an effort to break the chain of transmission of the Covid 19 virus in Banyuwangi Regency.